'Speaking Truth' Protects Underrepresented Minorities' Intellectual Performance and Safety in STEM - Avi Ben-Zeev; Yula Paluy; Katlyn Milless; Emily Goldstein; Lyndsey Wallace; Leticia Marquez-Magana; Kirsten Bibbins-Domingo; Mica Estrada (MDPI AG, 2017)
We offer and test a brief psychosocial intervention, Speaking Truth to EmPower (STEP), designed to protect underrepresented minorities' (URMs) intellectual performance and safety in science, technology, engineering, and math (STEM). STEP takes a 'knowledge as power' approach by: (a) providing a tutorial on stereotype threat (i.e., a social contextual phenomenon, implicated in underperformance and early exit) and (b) encouraging URMs to use lived experiences for generating be-prepared coping strategies. Participants were 670 STEM undergraduates [URMs (Black/African American and Latina/o) and non-URMs (White/European American and Asian/Asian American)]. STEP protected URMs' abstract reasoning and class grades (adjusted for grade point average [GPA]) as well as decreased URMs' worries about confirming ethnic/racial stereotypes. STEP's two-pronged approach-explicating the effects of structural 'isms' while harnessing URMs' existing assets-shows promise in increasing diversification and equity in STEM.